A review on nanofiber reinforced aerogels for energy storage and conversion applications. (February 2022) - Chhetri, Kisan; Subedi, Subhangi; Muthurasu, Alagan; Ko, Tae Hoon; Dahal, Bipeen; Kim, Hak Yong
Highlights: We have best tried to cover nanofiber reinforced aerogels for energy applications. Many review articles are published covering nanofiber and aerogel materials separately. Focused on collecting most recent and reliable sources and concise writing. Manufacturing technologies, application, and future perspectives are well summarized. A fascinating table-comparison with abridged description is provided. Abstract: This article provides an overview of the development of nanofibrous aerogels focusing on the carbon and polymer nanofiber reinforced aerogels. Aerogels are prepared by replacing the solvent by air conserving the pores and networks in bulk. They exhibit high porosity, ultra-lightness, and large specific surface area. Due to such gifted properties, aerogels are promising candidates for energy conversion and storage applications. In addition, nanofiber reinforced aerogels provide additionalmechanical stability. Unlike the frameworks created by interconnected particles in traditional inorganic aerogels, nanofibers can form chemically cross-linked and physically intertwined three-dimensional networks, thus providing good flexibility to the aerogels. This review summarizes current research progress in the manufacturing techniques, properties, and applications in energy conversion and storage of nanofiber reinforced aerogels . Various natural and synthetic nanofibers, including electrospun nanofibers and nano-cellulose, and carbon nanofibers, were obtained from corresponding organic precursors. Typical applications in supercapacitors, secondary batteries, electrocatalysts for oxygen reduction reactions occurring at fuel cells, and overall water splitting are presented. Finally, the challenges and future perspectives of nanofiber-reinforced aerogels are discussed. Graphical abstract: Image, graphical abstract